Gender and age differences in conflict management within small businessess - Werner Havenga (SA Journal of Human Resource Management, 2008)
The objective of this exploratory study was to establish, through the application of the Rahim Organisational Inventory (ROC II) instrument, how the gender and age status of owners/managers of small businesses relate to the application of different conflict-handling styles. The sample of 68 participants was taken using a convenience sampling technique to ensure representation from the strata of the 102 small businesses. Analysis of variances was used to determine if differences exist in conflict-handling styles within the gender and age status groups. The results of the statistical analysis done revealed that slight to significant variances were found, which are discussed accordingly.